Teriparatide treatment patterns in osteoporosis and subsequent fracture events: a US claims analysis - Bonafede, M. M. (Osteoporos Int, 2015)
SUMMARY: The objective of this study was to describe the risk of fragility-related fractures in the 2 years following teriparatide initiation. In an administrative claims analysis of over 11,407 patients, approximately one in eight patients had a new or recurrent fragility-related fracture in the 2 years following teriparatide initiation. INTRODUCTION: The objective of this study was to describe the risk of fragility-related fractures in the 2 years following the initiation of teriparatide in a real-world setting. METHODS: This retrospective study used data from the 2002 to 2011 MarketScan® Commercial and Medicare Supplemental Databases to identify patients 50 years and older with a diagnosis of osteoporosis (ICD-9-CM code 733.0x) who were initiating teriparatide. Patients were required to have continuous medical and pharmacy benefit coverage for the 12 months prior to and 24 months following teriparatide initiation (index event). Teriparatide treatment patterns (persistence and adherence) were described, as was the use of antiresorptive therapy. The primary study outcome was the presence of a new or recurring fragility fracture following the initiation of teriparatide. RESULTS: A total of 11,407 patients met the study criteria (mean age = 69.5, standard deviation = 10.6 years; 92.0 % female). One in four (25.6 %) patients had fragility fracture claims in the year prior to teriparatide initiation, of which 64.0 % were on existing antiresorptive therapy. Overall, 13.4 % (n = 1527) of patients had a new or recurrent fracture during the 2-year follow-up period. Forty-eight percent of patients on teriparatide treatment were considered persistent; fragility fractures were more common among patients nonpersistent with teriparatide (15.2 %) than among those persistent with teriparatide (11.4 %). A higher fracture rate (35.7 %) was observed in the cohort with previous fragility fracture then those without pre-index fractures (24 %). CONCLUSION: More than 13.4 % of patients had new or recurrent fragility-related fractures during the 2 years following the initiation of teriparatide; these fractures were more in common in patients with pre-existing fractures and the patients who were nonpersistent with teriparatide.